Optimizing the electric field around solid and core–shell alloy nanostructures for near-field applications. Issue 31 (25th July 2016) - Montaño-Priede, Luis; Peña-Rodríguez, Ovidio; Rivera, Antonio; Guerrero-Martínez, Andrés; Pal, Umapada
Abstract : Understanding the variations of the near electric field around plasmonic nanoparticles is very important for several applications where the interactions occur close to the surface of the nanoparticle. Abstract : The near electric field enhancement around plasmonic nanoparticles (NPs) is very important for applications like surface enhanced spectroscopies, plasmonic dye-sensitized solar cells and plasmon-enhanced OLEDs, where the interactions occur close to the surface of the NPs. In this work we have calculated the near-field enhancement around solid and core–shell alloy NPs as a function of their geometrical parameters and composition. We have found that the field enhancement is lower in the Au x Ag1− x alloys with respect to pure Ag NPs, but it is still high enough for most near-field applications. The higher order modes have a stronger influence over the near-field due to a sharper spatial decay of the near electric field with the increase of the order of multipolar modes. For the same reason, in Au x Ag1− x @SiO2 core–shell structures, the quadrupolar mode is dominant around the core, whereas the dipolar mode is predominant around the shell. The LSPR modes can have different behaviours in the near- and the far-field, particularly for larger particles with high Ag contents, which indicates that caution must be exercised for designing plasmonic nanostructures for near-field applications, as the variations of the LSPR in the near-field cannot be inferred from those observed in the far-field. These results have important implications for the application of gold–silver alloy NPs in surface enhanced spectroscopies and in the fabrication of plasmon-based optoelectronic devices, like dye-sensitized solar cells and plasmon-enhanced organic light-emitting diodes.